The Development of Arabic Language Learning Media Based on Google Site for Class VIII Students of Madrasah Tsanawiyah Negeri 2 Deli Serdang - Khairunnisa Khairunnisa; Akmal Walad Ahkas (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2023)
This research aims to produce and describe a product for developing Arabic language learning media based on Google Sites. Furthermore, a media validation test was carried out in class VIII Madrasah Tsanawiyah Negeri 2 Deli Serdang to determine the feasibility and quality of Google Sites-based Arabic learning media. The method used is a research and development method using the ADDIE development model developed by Dick and Carry which consists of five stages, namely analysis, design, development, implementation and evaluation. The data collection instrument used was a questionnaire of expert validation sheets, Arabic teacher response questionnaires and student responses. This media was validated by two expert validators, namely the media expert validator obtained an average percentage value of 88% with a very feasible category and the material expert validator obtained an average percentage value of 85% with a very feasible category. The Arabic teacher's response to the media obtained a percentage of 97% in the very decent category. Meanwhile, students' responses to the media obtained a percentage of 96% with a very decent category. Based on the data obtained, it can be concluded that Google Sites-based Arabic learning media for class VIII students of Madrasah Tsanawiyah Negeri 2 Deli Serdang is feasible to use in the learning process.